Statistics in Action: A Canadian Outlook Edited by J.F.Lawless. Boca Raton, Florida: CRC Press2014 384 pages. $185.00 (hardback). ISBN 9781482236231. (2nd August 2018) - Chambers, Ray
Abstract : A Review of Statistics in Action: A Canadian Outlook